Profile of atezolizumab in the treatment of metastatic non-small-cell lung cancer: patient selection and perspectives - Facchinetti F; Bordi P; Leonetti A; Buti S; Tiseo M (Dove Medical Press, 2018)
Francesco Facchinetti, Paola Bordi, Alessandro Leonetti, Sebastiano Buti, Marcello Tiseo Medical Oncology Unit, University Hospital of Parma, Parma, Italy Abstract: Programed cell death-1/programed death ligand-1 (PD-1/PD-L1) blockade represents an affirmed reality in the treatment of advanced non-small-cell lung cancer (NSCLC) patients. Atezolizumab, an anti-PD-L1 agent, figures among the drugs that provide previously unenvisaged outcomes in the pretreated setting of metastatic NSCLC. Increasing evidence vouches for the early administration of PD-1/PD-L1 blockers in untreated patients, encompassing atezolizumab combinations with chemotherapy and the anti-angiogenic agent bevacizumab. Moreover, the development of atezolizumab allowed to derive several hints regarding clinical and immunological factors predictive of its activity and efficacy, some of them exclusive among this class of drugs. This review provides an overview of atezolizumab development throughout clinical trials toward its applicability in the routine practice, with a particular focus on patient selection based on clinical and immune-related factors. Keywords: non-small cell lung cancer, NSCLC, immune checkpoint blockers, ICB, PD-1, PD-L1, atezolizumab development, biomarkers